Is Primatology an Equal-Opportunity Discipline? - Addessi, Elsa; Borgi, Marta; Palagi, Elisabetta (PLOS ONE, 2012)
The proportion of women occupying academic positions in biological sciences has increased in the past few decades, but women are still under-represented in senior academic ranks compared to their male colleagues. Primatology has been often singled out as a model of “equal-opportunity” discipline because of the common perception that women are more represented in Primatology than in similar fields. But is this indeed true? Here we show that, although in the past 15 years the proportion of female primatologists increased from the 38% of the early 1990s to the 57% of 2008, Primatology is far from being an “equal-opportunity” discipline, and suffers the phenomenon of “glass ceiling” as all the other scientific disciplines examined so far. In fact, even if Primatology does attract more female students than males, at the full professor level male members significantly outnumber females. Moreover, regardless of position, IPS male members publish significantly more than their female colleagues. Furthermore, when analyzing gender difference in scientific productivity in relation to the name order in the publications, it emerged that the scientific achievements of female primatologists (in terms of number and type of publications) do not always match their professional achievements (in terms of academic position). However, the gender difference in the IPS members' number of publications does not correspond to a similar difference in their scientific impact (as measured by their H index), which may indicate that female primatologists' fewer articles are of higher impact than those of their male colleagues.